Application of a Simple and Sensitive Electrochemical Sensor in Simultaneous Determination of Paracetamol and Ascorbic Acid. Issue 9 (2nd September 2021) - Deng, Peihong; Feng, Jinxia; Xiao, Jingyun; Wei, Yanping; Liu, Xia; Li, Junhua; He, Quanguo
Abstract : A new electrochemical sensor for the quick determination of both paracetamol (ACOP) and ascorbic acid (AA) was prepared using an acetylene black paste electrode modified with polyvinylpyrrolidone and graphene composite (PVP-GR/ABPE). Second derivative linear sweep voltammetry (SDLSV) and cyclic voltammetry (CV) were then used to investigate the electrochemical behavior of both ACOP and AA on this PVP-GR/ABPE. The results demonstrate that the two analytes have good resolution and strong electrochemical signal responses. Due to the interconnected effects of PVP, GR, and AB ternary composite, the designed electrode has several beneficial characteristicsincluding good adsorption ability, significant specific surface area, and good conductivity. The voltammetric responses of ACOP and AA on the PVP-GR/ABPE show that the modified electrode displayed good electrocatalytic properties for the chemical reactions of both ACOP and AA, with the linear range of 0.01–100 μ M for ACOP and the linear range of 6–1000 μ M for AA. The detection limits of 6.0 nM (ACOP) and 1.0 μ M (AA) were obtained, respectively. The sensor has successfully been used in the measurement of ACOP and AA in real samples, indicating that this method is potentially applicable for routine biomedical and chemical sensing in vitro diagnostically.